FUNGSI SIMAAN AL-QUR’AN BAGI SANTRI PONDOK PESANTREN SUNAN PANDANARAN, SLEMAN, YOGYAKARTA - Yahya, Mohamad (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2017)
This article focuses on function of simaan al-Qur’an for santri-mahasiswa of Pondok Pesantren Sunan Pandanaran (PPSPA), Sleman, Yogyakarta. This study uses Bronislaw Malinowski’s functionalism theory. Method of this study is observation-participation, interview, and literal documentary. The conclusion of this study that simaan al-Qur’an, for santri-mahasiswa of PPSPA, is not only has the function of religion. Furthermore, simaan al-Qur’an for santri-mahasiswa of PPSPA is a cultural system that has very complex element. The complexities of these elements are in line with their various functions; social, cultural, economical,political power, promotional, and educational. These interconnections and inter-functions can not be separated and tied to one another. Therefore, the activity of simaan al-Qur’an, as a cultural system, has a function to meet the psycho-biological needs of santri-mahasiswa in living their lives.